Javanese folklore with moral values: An impactful context in learning relations and functions - Prahmana, Rully Charitas Indra; Risdiyanti, Irma; Peni, Nur Robiah Nofikusumawati; Ristiana, Novita; Ramadhani, Rahmi (Journal on Mathematics Education, 2025)
Indonesia, particularly the Java region, is home to a wealth of folklore rich in moral teachings. Among these, the story of Rama and Sinta is one of the most prominent, and upon initial investigation, it reveals an underlying presence of mathematical concepts, particularly relations and functions. Despite this potential, there is a lack of research on integrating such cultural elements into the teaching of mathematics. This study aims to fill this gap by exploring the use of the Rama and Sinta narrative as a contextual tool for teaching relations and functions. Following the design research method within the Ethno-Realistic Mathematics Education (Ethno-RME) framework, we developed instructional materials for seventh-grade students at a public school in Magelang, Central Java, Indonesia. These materials, consisting of both student and teacher books, were designed to contextualize the mathematical concepts of relations and functions within the cultural narrative. The resulting learning trajectory, consisting of five interconnected activities, not only deepened students' understanding of the mathematical concepts but also reinforced the moral lessons embedded in the folklore. This paper details the development process, implementation, and outcomes of this culturally responsive approach, contributing valuable insights into the integration of local cultural narratives with core mathematical concepts to enhance the learning experience.